(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
That the government sector takes a big place in the countries and represents a significant role in the face of challenges and adaptation to the important and necessary changes that occur today, including the use of electronic. The electronic computer is a requirement of modern technology in various fields of science, including accounting, Because it derives its entity and content from the spirit of society and its mentality in all its branches, especially the subject of the research system of government accounting Because of its impact on the planning and financial implementation, especially in the preparation and implementation of the State budget, along with expenditure and revenue. Addressing tells us that the first of the search of the subject of the study of contemporary Governmental Accounting Concept, And most important functions and characteristics. The tells us that included the concept of the electronic government elements and their impact on the development of the organizations, the third tells us that the applied aspects and test the hypothesis Search. The research found that electronic systems had an expected impact on the pillars of the government accounting information system; this is necessary requirement to build a framework that corresponds to that system. The research recommended that the government accountant should be qualified to support theoretical advocacy and the practical need to move towards an electronic government accounting information system.